Algerian Anthropology in it’s French version - benchaibi, mohamed (Journal of Social Sciences and Humanities, 2021)
The anthropological field was characterised previously by studying what seems to be strange and traditional. This is why the French colonialism studied the Algerian society in its strange and traditional dimention , aiming at serving its objectives . At the same period. There was another kind of anthropology, the academic one that inspired Germaine Tillion who devoted her works to enrich this kind of disciplines. She was supporting politicaly the Algerian issue in order to stop violence towards Algerian people, through using the descriptive method . The purpose is to present an occidental person who was concerned and devoted most of her work about Algeria, during that period as a witness in the field by excellence .The scholar was ready every time to register the events and observations according to its chronological order, by which her field work became an important source to understand the social history of the Algerien society.